2016
DOI: 10.1038/srep30404
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine activity of BDNF induced by the STAT3 signaling pathway causes prolonged TrkB activation and promotes human non-small-cell lung cancer proliferation

Abstract: Brain-derived neurotrophic factor (BDNF) is a member of the neurotrophin superfamily, which has been implicated in the pathophysiology of the nervous system. Recently, several studies have suggested that BDNF and/or its receptor, tropomyosin related kinase B (TrkB), are involved in tumor growth and metastasis in several cancers, including prostate cancer, neuroblastoma, pancreatic ductal carcinoma, hepatocellular carcinoma, and lung cancer. Despite the increasing emphasis on BDNF/TrkB signaling in human tumors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 27 publications
5
38
0
Order By: Relevance
“…To elucidate mechanisms by which STAT3 inhibition might enhance the sensitivity of NB cells to cisplatin, we evaluated the DNA damage response pathway by Western analysis. In response to DNA damage, ATM and ATR are activated leading to activation of H2AX as well as their respective downstream targets Chk2 and Chk1 (33, 34). Activation of both the ATM and ATR DNA damage response pathways are detected after cisplatin treatment as indicated by the increases in phosphorylation of their respective downstream targets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To elucidate mechanisms by which STAT3 inhibition might enhance the sensitivity of NB cells to cisplatin, we evaluated the DNA damage response pathway by Western analysis. In response to DNA damage, ATM and ATR are activated leading to activation of H2AX as well as their respective downstream targets Chk2 and Chk1 (33, 34). Activation of both the ATM and ATR DNA damage response pathways are detected after cisplatin treatment as indicated by the increases in phosphorylation of their respective downstream targets.…”
Section: Resultsmentioning
confidence: 99%
“…In NB cells, high-level expression of wild-type ALK in cells constitutively expressing putative ALK ligands (31) or mutations in ALK (32) contribute to levels of P-STAT3. Although not systematically studied, growth factors known to be produced by NB cells, such as IGF-1 (33), BDNF (34, our unpublished data) stimulate increases in P-STAT3. These factors as well as growth factors contained in serum may contribute to the levels of P-STAT3 detected in NB cells cultured in vitro .…”
Section: Discussionmentioning
confidence: 95%
“…25 Recently, there has some evidence confirmed that BDNF and/or its receptor TrkB play roles in several cancers, including gastric cancer, 26 cervical cancer, 27 and glioma. 25 Recently, there has some evidence confirmed that BDNF and/or its receptor TrkB play roles in several cancers, including gastric cancer, 26 cervical cancer, 27 and glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, BDNF has been shown to promote non-small lung cancer proliferation in an autocrine manner and metastasis of neuroblastoma through STAT3 and PI3K and MAPKsingalling pathway, respectively [21, 31]. …”
Section: Discussionmentioning
confidence: 99%